2021
DOI: 10.1128/mbio.02243-21
|View full text |Cite
|
Sign up to set email alerts
|

The Epstein-Barr Virus Oncogene EBNA1 Suppresses Natural Killer Cell Responses and Apoptosis Early after Infection of Peripheral B Cells

Abstract: Epstein-Barr virus (EBV) is a ubiquitous human pathogen, infecting up to 95% of the world’s adult population. Initial infection with EBV can cause infectious mononucleosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…Some of these are expressed during the lytic or prelatent phase, while others are more consistently expressed during the latent infection. For example, EBNA1 can induce CXCL12 to recruit regulatory T cells 69 and suppress NK cell responses by downregulating NKG2D ligands 70 . EBNA2 transcriptionally activates numerous genes involved in immune regulation, such as those encoding tumour necrosis factor (TNF) 71 , lymphotoxin-α 72 , IL-18R 73 and PDL1 (refs.…”
Section: Ebv Biology and Life Cyclementioning
confidence: 99%
“…Some of these are expressed during the lytic or prelatent phase, while others are more consistently expressed during the latent infection. For example, EBNA1 can induce CXCL12 to recruit regulatory T cells 69 and suppress NK cell responses by downregulating NKG2D ligands 70 . EBNA2 transcriptionally activates numerous genes involved in immune regulation, such as those encoding tumour necrosis factor (TNF) 71 , lymphotoxin-α 72 , IL-18R 73 and PDL1 (refs.…”
Section: Ebv Biology and Life Cyclementioning
confidence: 99%
“…The role of KDMs in the development and function of NK cells Natural killer (NK) cells are cytotoxic lymphocytes that rapidly fight against pathogens to maintain homeostasis [100][101][102][103]. NK cells play important roles during early viral infection by releasing granules containing perforin and granzymes and secreting critical Fig.…”
Section: Functions Of Kdms In T Lymphocytes Developmentmentioning
confidence: 99%
“…On the contrary, expression in EBV − gastric carcinoma (GC) cells or other epithelial cell carcinomas of the LMP2A protein that is important for maintaining EBV latency and inducing host cell transformation, had a dual effect on the expression of MICA and MICB: LMP2A, on the one hand, upregulated their transcripts and, on the other hand, decreased total protein amounts, which resulted in a net reduction of both ligands at the cell membrane, though the functional consequences were not investigated [ 101 ]. Another recent work, using primary B cells infected with EBV either wt or deficient for the expression of the EBNA1 oncoprotein as well as epithelial cell lines transduced with EBNA1-expressing or control vector, showed that EBNA1 downregulated ULBP1 and ULBP5 mRNA levels, likely by reducing activation of cellular stress responses and c-Myc, and protected newly infected B cells from NKG2D-dependent killing by NK cells [ 102 ]. Finally, two independent works showed that EBV encodes for two distinct microRNAs targeting NKG2DL mRNA molecules, both belonging to the BART family and expressed in all forms of latency as well as during virus replication.…”
Section: Nk/ebv-infected Cell Interactionsmentioning
confidence: 99%